A combined experimental and numerical investigation on projectiles penetrating into water-filled container. (October 2019) - Ren, Peng; Shi, Lu; Ye, Renchuan; Chai, Dongliang; Zhao, Wei; Wu, Jie; Zhang, Wei; Mu, Zhongcheng
Abstract: The experiments and numerical simulations of projectile penetrating into water-filled container with aluminum target plates were conducted. The motion of projectile and cavity evolution of hydrodynamic ram in water were assessed. The results show the propagation characteristics of initial shock wave of hydrodynamic ram in the container. The study presents that the plugging with outward deformation was the main failure mode of the target plates when the velocity of projectile was below 270 m/s. With the velocity of projectile increasing, the ultimate deformation of plates increased linearly and the petaling failure appeared on the rear plates. Four kinds of typical failure modes for plates of water-filled container were concluded through the combining results of experiment and simulation. In addition, the effect of plate thickness on the plastic deformation were discussed, and the quantitative relation among the deformation of target plates, velocity of projectile and plate thickness were established. Highlights: Experiments and numerical simulations were conducted to analyze the ultimate deformation and failure of water-filled container subjected to blunt projectile impact. The hydrodynamic ram including projectile motion, initial shock wave and cavity were investigated in water-filled container. Four different failure modes of target plates were observed: plastic deformation (mode I), plugging failure with plastic deformation (mode IIa and mode IIb ) and petaling failure with large plastic deformation (mode III). Effects of plate thickness and projectile velocity on the ultimate deformation of plates were assessed.